Neopentyl glycol-based radiohalogen-labeled amino acid derivatives for cancer radiotheranostics - Yuta Kaizuka; Hiroyuki Suzuki; Tadashi Watabe; Kazuhiro Ooe; Atsushi Toyoshima; Kazuhiro Takahashi; Koichi Sawada; Takashi Iimori; Yoshitada Masuda; Takashi Uno; Kento Kannaka; Tomoya Uehara (SpringerOpen, 2024)
Abstract Background L-type amino acid transporter 1 (LAT1) is overexpressed in various cancers; therefore, radiohalogen-labeled amino acid derivatives targeting LAT1 have emerged as promising candidates for cancer radiotheranostics. However, 211At-labeled amino acid derivatives exhibit instability against deastatination in vivo, making it challenging to use 211At for radiotherapy. In this study, radiohalogen-labeled amino acid derivatives with high dehalogenation stability were developed. Results We designed and synthesized new radiohalogen-labeled amino acid derivatives ([211At]At-NpGT, [125I]I-NpGT, and [18F]F-NpGT) in which L-tyrosine was introduced into the neopentyl glycol (NpG) structure. The radiolabeled amino acid derivatives were recognized as substrates of LAT1 in the in vitro studies using C6 glioma cells. In a biodistribution study using C6 glioma-bearing mice, these agents exhibited high stability against in vivo dehalogenation and similar biodistributions. The similarity of [211At]At-NpGT and [18F]F-NpGT indicated that these pairs of radiolabeled compounds would be helpful in radiotheranostics. Moreover, [211At]At-NpGT exhibited a dose-dependent inhibitory effect on the growth of C6 glioma-bearing mice. Conclusions [211At]At-NpGT exhibited a dose-dependent inhibitory effect on the tumor growth of glioma-bearing mice, and its biodistribution was similar to that of other radiohalogen-labeled amino acid derivatives. These findings suggest that radiotheranostics using [18F]F-NpGT and [123/131I]I-NpGT for diagnostic applications and [211At]At-NpGT and [131I]I-NpGT for therapeutic applications are promising.